Ang askal sa kalye Kalinaw The stray dog in kalinaw street - Evasco, Eugene Y. (Chikiting books, 2013)
"Jn Kalinaw street is a lucky askal, a stray dog who has five names; five families, and five breakfasts, lunches, snacks, and dinners every day. How will the askal pave the way for the people in the five homes that take care of her to get to know each other and become one? This story values respect for people, regardless of their beliefs, culture, appearances, and their socio-economic status."